PRODUCT PRICE PERCEPTIONS ON PRODUCT PURCHASING DECISIONS - Nur Hasmalawati; Rizka Dara Vonna; Vikra Oktariana (State Islamic University (UIN) Ar-Raniry, 2024)
Price is one of the important considerations for consumers to decide to buy something. This is because consumers certainly expect the money spent to match what is obtained. This study aims to determine the effect of price perception on product purchasing decisions at Tokokopikiri Banda Aceh. The research method used is quantitative research using a sample of 200 people. Data analysis using linear regression test. The results showed that there was an effect of perceived product prices on product purchasing decisions at Tokokopikiri Banda Aceh with a Sig value of 0.001 <0.05. The contribution given by product price perceptions to product purchasing decisions can be seen from the R-Square value, which is 0.634, it means that product price perceptions influence product purchasing decisions at Tokokopikiri Banda Aceh by 63.4%, while the rest is influenced by other variables, such as product quality and sales promotion. When wanting to buy a product, consumers must consider the price offered in accordance with the product produced. In addition, consumers must also be smart to pay attention to the quality and benefits of the products they get. Future researchers are expected to develop research on the factors that influence purchasing decisions using different data analyses, resulting in more accurate research.